Effects of a Plant Based Natural Alternative of Choline and Betaine as Replacements for Synthetic Choline in Broilers Diets - Avi, R.; Gonzalez, J.; Sol, C.; Horta, F.D.C.; Bouvet, R. (International Journal of Poultry Science, 2025)
Objective: This study aimed to assess the feasibility of replacing synthetic Choline Chloride (CC) with a natural Choline Alternative (NC) and betaine (BT) in broiler diets, focusing on their effects on broiler performance. Materials and Methods: Ten dietary treatments were tested on 3,000 male Ross-308 broiler chicks over a 42-day period, including varying levels of Natural Choline (NC), betaine (BT) and synthetic Choline Chloride (CC), with 10 replicates per treatment. Birds were housed in 100 pens, with each pen serving as an experimental unit. Results: The study found a significant effect of diet on BW at 42 days. Broilers fed 400 g/ton of either BT or NC exhibited higher BW compared to the control, birds fed with 200 g/ton of NC and broilers fed with CC. The most efficient Feed Conversion Ratio (FCR) was observed in broilers fed the combination of NC 100 g/ton and BT 200 g/ton, followed by those fed BT or NC at 200 g/ton each. No significant differences (p>0.05) were observed among these treatments. Broilers supplemented with CC and the control group showed the least efficient FCR. The combination of NC and BT showed better performance. Conclusion: These findings suggest that NC and BT can replace synthetic CC in broiler diets without compromising performance. Moreover, the combination of NC and BT may provide a synergistic benefit, potentially leading to better feed efficiency and growth performance. This indicates that natural choline alternatives can be a viable replacement for synthetic choline chloride in broiler nutrition.